Estimación de la vida útil de la humita precocida por métodos físico y químico mediante el factor de aceleración Q10 - Roman Marcillo, Diego Javier (2013)
The goal of this research was to estimate the humita lifetime according to storage temperature with the application of preservative (sorbic acid) and calculating the acceleration factor Q10. We studied the storage of humita at 0 to 10 °C, and two methods of application of sorbic acid (direct application and dipping). The experimental unit was 100g using a completely randomized design bifactorial AxB with three replicates. Sensory parameters were evaluated: taste, smell, color, texture, overall quality, chemical (pH, acidity), microbiological (molds and yeasts) and life cycle through linear regression equation proposed by Labuza and the acceleration factor Q10. In sensory analysis of a1b2 treatment presented the best average. The number of CFU/g does not exceed the limits allowed by the standard that is establish in INEN 1528 50x103UFC / g (In = 10.81) in most cases, except for the treatment a2b1. The pH in a1b2 and a1b1 treatments had the highest averages close to neutral. The days of life were 5.5, 0.9, 2.61 for treatments and the Q10 value obtained was 2.1. The longest lifetime is obtained at 0⁰C with direct application of preservative (sorbic acid). Q10 factor established that the temperature at 10⁰C is 2.1 times faster in degradation reactions.